Contribuições aos estudos computacionais de ressarcimento por danos elétricos devido a descargas atmosféricas diretas e indiretas - Almeida Junior, Afonso Bernardino de (2016)
This research is related with the development of improvements for supporting the consistency of the causal nexus between anomalous phenomena likely to occur in transmission and distribution networks and the occurrence of physical damage to consumer’s equipment. The work is focused on the subject of direct and indirect lightning strikes and the corresponding increase on the earth potential that may cause abnormal dielectric and thermal stresses on consumer devices. In line with these goals, this thesis is dedicated to two specific challenges. The first is related to the representation of grounding systems through earth electrodes, highlighting the main models proposed in the literature, regarding the linearity and non-linearity of the phenomena surrounding these. Using experimental data as reference values, investigations are carried out in order to check out the adherence degree between the existing models and the practical values. This allows for adopting the most appropriate strategy to represent the given effect. In the other hand, the work takes into account the ground potential rise phenomenon due indirect lightning. In this context, a methodology is proposed based on the images method, aimed at including this alternative way capable of causing the claimed damages. With the inclusion of the mentioned new features, the reimbursement analysis software is now able of evaluating refunding claims involving ground potentials rise at the occurrence of direct and indirect lightining strikes. Based on practical situations representing real cases, computational studies are performed in order to illustrated the new software version herein obtained.